Anatomia quantitativa e morfogênese da grama-tapete em função de doses de dejeto líquido de suínos - Travi, Magdalena Reschke Lajús (2012)
Leaf blade of carpet grass (Axonopus affinis Chase) fertilized with pig slurry (PS) was assessed for the tissue proportion, chemical composition (Experiment I) and morphogenesis (Experiment II). In 2008-09 the grassland was fertilized with rates of 0, 60, 120, 180, 240 and 300 m3 of PS/ha. In the third cut performed in March/2009 the grass leaf blades were sampled for quantification of proportion of epidermis (EPI), parenchyma (PAR), non-lignified vascular tissue (NLVT) and lignified vascular tissue + sclerenchyma (LVT+S). Samples of forage were taken to determine the percentage of the crude protein (CP), acid detergent fiber (ADF) and neutral detergent fiber (NDF). In 2009-2010 the morphogenesis was evaluated in the spring and summer of both years in response in response to the application of 0, 51, 102, 153, 204 and 255 m3 of PS/ha. The proportion of PAR and EPI was increased, and the proportion of LVT+S was reduced with increase of PS rates. There was no effect of fertilization on chemical composition, which presented 12.5%, 68.2% and 39.0% of CP, NDF and ADF, respectively. It was not observed any correlation between the proportion of tissues and chemical characteristics. Pig slurry increased the tiller density, canopy elongation rate, leaf elongation rate, leaf life span and leaf area index.